Differentiation of chemical reaction activity of various carbon nanotubes using redox potential: Classification by physical and chemical structures. (December 2015) - Tsuruoka, Shuji; Matsumoto, Hidetoshi; Castranova, Vincent; Porter, Dale W.; Yanagisawa, Takashi; Saito, Naoto; Kobayashi, Shinsuke; Endo, Morinobu
Abstract: The present study systematically examined the kinetics of a hydroxyl radical scavenging reaction of various carbon nanotubes (CNTs) including double-walled and multi-walled carbon nanotubes (DWCNTs and MWCNTs), and carbon nano peapods (AuCl3 @DWCNT). The theoretical model that we recently proposed based on the redox potential of CNTs was used to analyze the experimental results. The reaction kinetics for DWCNTs and thin MWCNTs agreed well with the theoretical model and was consistent with each other. On the other hand, thin and thick MWCNTs behaved differently, which was consistent with the theory. Additionally, surface morphology of CNTs substantially influenced the reaction kinetics, while the doped particles in the center hollow parts of CNTs (AuCl3 @DWCNT) shifted the redox potential in a different direction. These findings make it possible to predict the chemical and biological reactivity of CNTs based on the structural and chemical nature and their influence on the redox potential.